The importance of digitization and its impact on improving customer experience in Algerian financial institutions (trust) - Mekhlouf, Mohamed (The International tax journal, 2025)
Digitization is one of the most important technological tools transforming and influencing various aspects of life. Islamic financial institutions in Algeria are part of the digital transformation imposed by practical reality. These institutions have relied on digital technology to improve their services to clients and meet their needs effectively and quickly, enhancing their competitiveness in the Algerian financial market. This is a customer demand to facilitate various financial transactions, including withdrawals, transfers, deposits, and other financial transactions. Digitization in Islamic financial institutions is an urgent necessity imposed by practical reality for these institutions to be effective and address various challenges. Perhaps the most important of these challenges is retaining existing clients and attracting new ones by improving the performance of existing Islamic financial services and innovating new ones to maintain competitiveness in the financial market.